Electrocoagulation and electroflotation to reduce organic content and turbidity in simulated urban wastewater - Villon, Angel (2019)
In a normal coagulation / flocculation process, the coagulated / flocculated material is removed by sedimentation. The research proposal is to electrocoagulate and float them (electroflotation); For this, Al+3 and Fe+3 in-situ and oxygen and hydrogen are produced, in order to make this procedure more efficient (electroflotation), a pair of auxiliary electrodes is used, whose sole function is to produce these O2/H2 gases, This way the clots formed by the upper part of the system are removed. The simulated organic load comes from the reduction of the size of species such as proteins / meat, starches / cereals, cellulose / vegetables, fats / oils of vegetable and animal origin. The study was able to reduce turbidity of 1200-1300 NTU to values ​​below 16 NTU and values ​​of 3,400 mgL-1 of COD to values ​​below 500 mgL-1 of COD.